2013
DOI: 10.1103/physrevb.88.180509
|View full text |Cite
|
Sign up to set email alerts
|

s-wave pairing in the optimally doped LaO0.5F0.5BiSet al.

Abstract: We report on the magnetic and superconducting properties of LaO0.5F0.5BiS2 by means of zero-(ZF) and transverse-field (TF) muon-spin spectroscopy measurements (µSR). Contrary to previous results on iron-based superconductors, measurements in zero field demonstrate the absence of magnetically ordered phases. TF-µSR data give access to the superfluid density, which shows a marked 2D character with a dominant s-wave temperature behavior. The field dependence of the magnetic penetration depth confirms this finding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 30 publications
(46 reference statements)
4
52
0
Order By: Relevance
“…The parent compounds, AOBiS 2 (A = La, Ce, Th) [6,13] and SrFBiS 2 [14][15][16], are bad metals and show semiconducting-like behavior; however, theoretical studies employing the tight-binding model and density functional calculations predicted that electron doping in the BiS 2 system increases the density of states at the Fermi level [17,18], making electron doping a crucial tuning parameter for superconductivity. The pairing mechanism in both Bi 4 O 4 S 3 and LaO 0.5 F 0.5 BiS 2 has also been investigated; recent studies of the temperature dependence of the penetration depth by the tunnel diode oscillator technique revealed evidence for fully gapped, strongly-coupled s-wave superconductivity in the Bi 4 O 4 S 3 compound [19], and an s-wave character for LaO 0.5 F 0.5 BiS 2 was indicated in muon-spin spectroscopy measurements [20]. It has been suggested that superconductivity emerges in the vicinity of a chargedensity wave (CDW) and semiconducting-like behavior [6,21].…”
Section: Introductionmentioning
confidence: 99%
“…The parent compounds, AOBiS 2 (A = La, Ce, Th) [6,13] and SrFBiS 2 [14][15][16], are bad metals and show semiconducting-like behavior; however, theoretical studies employing the tight-binding model and density functional calculations predicted that electron doping in the BiS 2 system increases the density of states at the Fermi level [17,18], making electron doping a crucial tuning parameter for superconductivity. The pairing mechanism in both Bi 4 O 4 S 3 and LaO 0.5 F 0.5 BiS 2 has also been investigated; recent studies of the temperature dependence of the penetration depth by the tunnel diode oscillator technique revealed evidence for fully gapped, strongly-coupled s-wave superconductivity in the Bi 4 O 4 S 3 compound [19], and an s-wave character for LaO 0.5 F 0.5 BiS 2 was indicated in muon-spin spectroscopy measurements [20]. It has been suggested that superconductivity emerges in the vicinity of a chargedensity wave (CDW) and semiconducting-like behavior [6,21].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the symmetry of the superconducting gap has also been investigated theoretically and experimentally. These studies have suggested the isotropic s-, anisotropic s-, and d-wave symmetries as possible pairing symmetries 33,36,37 . Despite these studies described above, there is less conclusive empirical evidence for determining the pairing symmetry and for uncovering whether CDW instability occurs.…”
mentioning
confidence: 99%
“…1 , the electronic and lattice structures of various BiS 2 -based superconductors have been attracting great interest including REO 1−x F x BiS 2 (RE: rare earth elements) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . In a typical REO 1−x F x BiS 2 system, REO 1−x F x block layer and BiS 2 layer are alternatively stacked each other, and F substitution for O is considered as an electron dope to the electronically active BiS plane 17 whereas it has continuously been found that actual carrier concentration is always smaller than its nominal value [18][19][20] .…”
mentioning
confidence: 99%